Shear Walls Induced RC Structures (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years, the construction of skyscrapers has been on the rise to overcome the shortage of land. These buildings are subject to an external lateral force, such as an earthquake and wind pressure. Pushover analysis (POA) has been broadly used in predicting the earthquake response of structures, and shear walls have been shown to be lateral drag elements. Therefore, in the present work, the effect of placing a shear wall on the periphery symmetrically, the periphery asymmetrically and in the center of the building is performed using the ETABS software. Using the response spectrum methodand thetime history method, a dynamic analysis is performed. Responses such as floor shear, floor displacement, and lateral floor shifts due to seismic forces are evaluated for various locations of the shear wall. According to the results and analysis, the shear wall on the symmetrical periphery of the structure is reducing the displacement and deviation of the floor compared to other cases.